Vertical Conflict on Sea Sand Mining Activities in Lampung; Law Enforcement and Sociological Approach - Bayu Sujadmiko; Refi Meidiantama (Administrative and Environmental Law Review, 2022)
The lack of law enforcement related to marine sand mining activities, which is not in line with the community in Lampung Province, certainly causes many problems. It can cause quite a high social conflict and environmental ecosystems as well as ecological disasters. In addition, the impact of the sea sand mining permit also overlaps the allocation of coastal areas and small islands. This article aims to analyze law enforcement against marine sand mining activities that conflict with the community in Lampung Province. This study uses an empirical normative method with a qualitative analysis model. The informant was from WALHI by Irfan Tri Musri and some miners. The results show that law enforcement for sea sand mining has to start from the law formulation, application, and execution stages of law enforcement. Another important thing is prevention efforts to control environmental impacts that must be performed by maximizing the usage of the monitoring and licensing instruments. In addition, Lampung Province Regulation Number 1 of 2018 concerning Zoning Plans for Coastal Areas and Small Islands must be appropriately implemented for law enforcement because it is sufficient to accommodate the interests of the community. The most dominant inhibiting factors in law enforcement of marine mining in conflict with the community in Lampung Province are statutory factors and law enforcement officers who are not firm in enforcing the law of sea sand mining.